Penjadwalan Perawatan dan Perbaikan Penggiling Tepung Beras Kapasitas 15 kg/Jam dengan Metode IRRO - Akmal Firdausy Fawaz Winahadi; Syamsul Hadi; Aufasiena Rafief Huda; Wahyu Endro Putra Rhendyansyah; Niki Cahyo Prasetyo (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
Frequent damage to the grinding disc components and the transmission system of the 15 kg/hour rice flour grinder is a problem faced. The purpose of scheduling component maintenance and repairs is to obtain predictions of maintenance and repair schedules and costs for the period 2026. The component maintenance and repair scheduling method includes examining previous period maintenance and repair data, applying the inspection-replace-repair-overhaul (IRRO) method, assessing component conditions, estimating component life, estimating technician costs, estimating supporting work equipment and supporting materials to be used in maintenance, estimating the time for replacing spare parts or reinstalling components after repair, estimating maintenance and repair costs in 2026, and calculating the maintenance cost to profit ratio. The results of component maintenance and repair scheduling show that the maintenance cost in 2026 is Rp 1,370,000,- with an estimated annual profit potential of Rp 21,600,000, and the maintenance cost to profit ratio is 6.3%, which implies that the 15 kg/hour rice flour grinder is still quite prospective and feasible to use for the next few years.